KESALAHAN GRAMMAR PADA MAKALAH MAHASISWA PROGRAM STUDI BAHASA INGGRIS ABA BSI JAKARTA - Baiatun Nisa (LPPM Universitas Bina Sarana Informatika, 2017)
The aims of the research is to know grammatical mistakes in the text Introduction on English students’ papers, and it is also to know the cause of the occurrence of such errors. This case study was undertaken within an English Department at the Academy of Foreign Language of Bina Sarana Informatika (ABA BSI) Jakarta academic year 2015/2016. This research used descriptive method with content and discourse analysis on the text. This research was conducted in study subjects of Essay Writing. The result showed that students still do not understand enough the structure of a paragraph. The errors occurred in the technical understanding of the target language. But even so there was also little evidence of the influence of the mother tongue of the mistakes that students made. Students have to understand more the subject-verb agreement.